Replicating Roaches: A Preregistered Direct Replication of Zajonc, Heingartner, and Herman’s (1969) Social-Facilitation Study - Halfmann, Emma; Bredehöft, Janne; Häusser, Jan Alexander (Psychological science, 2020)
Fifty years ago, Zajonc, Heingartner, and Herman (1969) conducted a famous experiment on social enhancement and inhibition of performance in cockroaches. A moderating effect of task difficulty on the effect of the presence of an audience, as revealed by impaired performance in complex tasks and enhanced performance in simple tasks, was presented as the major conclusion of this research. However, the researchers did not test this interaction statistically. We conducted a preregistered direct replication using a 2 (audience: present vs. absent) × 2 (task difficulty: runway vs. maze) between-subjects design. Results revealed main effects for task difficulty, with faster running times in the runway than the maze, and for audience, with slower running times when the audience was present than when it was absent. There was no interaction between the presence of an audience and task difficulty. Although we replicated the social-inhibition effect, there was no evidence for a social-facilitation effect.